2017
DOI: 10.1002/ejp.1027
|View full text |Cite
|
Sign up to set email alerts
|

Pain in knee osteoarthritis is associated with variation in the neurokinin 1/substance P receptor (TACR1) gene

Abstract: This study contributes to the knowledge of the genetics of painful osteoarthritis, a condition which affects millions of individuals worldwide. Specifically, a contribution from the TACR1 gene to modulating pain sensitivity in osteoarthritis is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…central pain pathways and genetic factors. 7,33,35 This study also shows that the functional status of the shoulder, evaluated according to the CS-Score items "mobility" and "strength" are clearly associated with the severity of the radiographic articular changes. This might be explained by the fact that a decreased joint volume, a tight capsule, osteophytes and the deformation of the articular surface may cause a mechanical restriction of the joint motion as well as a reduced ability to raise and hold a speci c weight in a given position.…”
Section: Discussionsupporting
confidence: 60%
“…central pain pathways and genetic factors. 7,33,35 This study also shows that the functional status of the shoulder, evaluated according to the CS-Score items "mobility" and "strength" are clearly associated with the severity of the radiographic articular changes. This might be explained by the fact that a decreased joint volume, a tight capsule, osteophytes and the deformation of the articular surface may cause a mechanical restriction of the joint motion as well as a reduced ability to raise and hold a speci c weight in a given position.…”
Section: Discussionsupporting
confidence: 60%
“…Second, SF SP has been reported in KOA patients [22], and the level of SP has been correlated with pain relief after treatment with medication [46]. The SP receptor (TACR1) gene has also been correlated with pain in KOA [47], though to date, no study has reported a link between SP and pain intensity. Our study showed no correlation between SF SP and OA pain.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, neurogenic SP could act on NK1 in the cartilage cell membrane in a paracrine manner, thus accelerating cartilage degeneration. In animal models and human studies of OA, SP, and NK receptors have been linked to joint pain, inflammation, and injury (77,78).…”
Section: Pathological Effects-osteoarthritismentioning
confidence: 99%